Perception of Virtual Class during the Covid-19 Pandemic: A Case Study of Tribhuvan University - Yadav, Deo Narayan (Journal of Population and Development, 2021)
Assessing acceptance level of virtual classroom technology has become important at the Tribhuvan University after Covid-19 pandemic. This article has investigated the acceptance level of virtual classroom from teachers and students involved in BIT course delivery and previous experiences of virtual classroom from various research articles. The assessment framework is based on the setting of virtual classroom at Patan Multiple Campus (PMC) immediately after the COVID-19pandemic lockdown using “Office 365 A1 education free version of MS Teams” in pmc.edu.np domain and Moodle-Open-source learning platform. The BIT courses were delivered through virtual classrooms, which were accessed by both students and teachers. The conclusion of the study is that the use of virtual classroom as an alternative mode of course delivery is accepted by teachers and students, but with different levels of acceptance. The study focuses on students and teachers involved in one particular BIT classes and it needs to further research in other course domain and in larger scale. This paper provides information that will be the interest of Tribhuvan University in implementing virtual classroom as an alternate mode of course delivery.